TINGKAT KEPUASAN TAMU TERHADAP KUALITAS PELAYANAN ROOM ATTENDANT DI CK TANJUNGPINANG HOTEL & CONVENTION CENTRE - WELLI BRAHAM KURNIAWAN; BOYCCE SYAHYUDDA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2023)
This study aims to measure the level of guest satisfaction on service quality of room attendant at the CK Tanjungpinang Hotel & Convention Center. The data in this study were obtained by distributing questionnaires to guests staying overnight with a sample of 100 respondents. The research method used is a quantitative descriptive research method using data analysis methods in the form of instrument tests (validity and reliability tests) and mean statistical tests (average value) using Microsoft Excel. The results of the study using the mean statistical test method obtained that of the five elements of service quality, the tangible element received the highest average value with a value of 3.46 and the reliability element received the lowest average value with a value of 3.16.